Penyelenggaraan Pendaftaran Tanah Sistematis Lengkap (PTSL) yang Berkepastian Hukum - Alamal Huda, Nur Ayu; Silviana, Ana (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Due to the complexity of land registration regulations, it is difficult to achieve legal certainty regarding PTSL products. Because there are differences in laws and regulations, this is the main teaching. ATR/BPN Ministerial Decree No. Article 6 of 2018 concerning PTSL. Based on the principles of simple, fast, smooth, safe, fair and open, this Ministerial Regulation aims to realize legal certainty and legal protection of community land rights for the benefit of the nation's welfare and prosperity. and to reduce and avoid land conflicts. The inspection is fair and most likely the manufacturer will find out and dissect the valid reasons why the PTSL goods do not have credibility; and realizing the ideal form of PTSL product and legal certainty. This paper utilizes library research to refer to library data in the form of books, scientific journals, statutory regulations and other supporting information related to research interests. The results of the inspection here of PTSL goods do not yet have legal certainty which must be seen from the instructions as the limit of legal certainty. The ideal type of legally enforceable PTSL item is recognized through: (i) encapsulation of rechtcadaster guidelines; (ii) projection of level one and level two PTSL structures; (iii) improving IT technology in the form of database maintenance.